May be:
frst (Bar a) = a
frst (Baz a a') = a
scnd (Bar a) = a
scnd (Baz a a') = a'
instance Monad Foo where
return = Bar
Bar x >>= f = f x
Baz x y >>= f = Baz (frst (f x)) (scnd (f y))
This definition is inspired by the definition (>>=)
for (Bool ->)
. Ask me if it’s not clear how.
Let them check the laws. The laws of " return
is unit" are quite simple:
return x >>= f
= Bar x >>= f
= f x
m >>= return
= case m of
Bar x -> return x
Baz x y -> Baz (frst (return x)) (scnd (return y))
= case m of
Bar x -> Bar x
Baz x y -> Baz x y
= m
I believe that I have ascertained that it (>>=)
is an “associative” law, but I am sure that this evidence is completely unreadable to anyone else ... I urge you to try to prove it yourself and turn to my calculations as a fraud if you stuck.
m >>= (\v -> f v >>= g)
= case m of
Bar x -> (\v -> f v >>= g) x
Baz x y -> Baz (frst ((\v -> f v >>= g) x))
(scnd ((\v -> f v >>= g) y))
= case m of
Bar x -> f x >>= g
Baz x y -> Baz (frst (f x >>= g)) (scnd (f y >>= g))
= case m of
Bar x -> case f x of
Bar y -> g y
Baz a b -> Baz (frst (g a)) (scnd (g b))
Baz x y -> Baz (frst l) (scnd r) where
l = case f x of
Bar a -> g a
Baz a b -> Baz (frst (g a)) (scnd (g b))
r = case f y of
Bar a -> g a
Baz a b -> Baz (frst (g a)) (scnd (g b))
= case m of
Bar x -> case f x of
Bar y -> g y
Baz a b -> Baz (frst (g a)) (scnd (g b))
Baz x y -> Baz (frst (g (frst (f x))))
(scnd (g (scnd (f y))))
= case m of
Bar a -> case f a of
Bar x -> g x
Baz x y -> Baz (frst (g x)) (scnd (g y))
Baz a b -> case Baz (frst (f a)) (scnd (f b)) of
Bar x -> g x
Baz x y -> Baz (frst (g x)) (scnd (g y))
= case v of
Bar x -> g x
Baz x y -> Baz (frst (g x)) (scnd (g y))
where v = case m of
Bar a -> f a
Baz a b -> Baz (frst (f a)) (scnd (f b))
= case m >>= f of
Bar x -> g x
Baz x y -> Baz (frst (g x)) (scnd (g y))
= (m >>= f) >>= g
edit , , (Bool ->)
, . , :
instance Monad (e ->) where
m >>= f = \e -> f (m e) e
data Pair a = Pair a a
, Bool -> a
Pair a
:
to :: Pair a -> (Bool -> a)
to (Pair false true) = \bool -> case bool of
False -> false
True -> true
from :: (Bool -> a) -> Pair a
from f = Pair (f False) (f True)
, from
to
. : Bool -> a
" ". , (e ->)
Monad
Pair
? , , , . , :
instance Monad Pair where
return x = from (return x)
m >>= f = from (to m >>= to . f)
" ":
return x
= from (return x)
= from (\e -> x)
= Pair ((\e -> x) False) ((\e -> x) True)
= Pair x x
m@(Pair false true) >>= f
= from (to m >>= to . f)
= from (\e -> (to . f) (to m e) e)
= from (\e -> to (f (to m e)) e)
= Pair (g False) (g True) where
g = \e -> to (f (to m e)) e
= Pair (to (f (to m False)) False) (to (f (to m True)) True)
= Pair (case f (to m False) of Pair false true -> false)
(case f (to m True ) of Pair false true -> true )
= Pair (case f false of Pair false true -> false)
(case f true of Pair false true -> true )
, , (Bool ->)
, :
frstPair (Pair false true) = false
scndPair (Pair false true) = true
instance Monad Pair where
return x = Pair x x
Pair false true >>= f = Pair (frstPair (f false)) (scndPair (f true))
, , (>>=)
, Foo
.
edit 2 (!) . :
type Foo = Product Identity Maybe
Product
. , :
instance Monad Foo where
return x = Baz x x
Bar x >>= f = Bar (frst (f x))
Baz x y >>= f = case f y of
Bar a -> Bar (frst (f x))
Baz a b -> Baz (frst (f x)) b
, "" - Bar
return
Bar
Baz
bind - "" - Baz
return
Baz
Bar
bind. , ! , Monad
Product
(, ).